Empire Falls and How A Disillusioned Society of the Early 21st Century Resorts to Romantic Tendencies - M Irfan Zamzami (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
This paper is principally aimed at analyzing the theme of Richard Russo’s Empire Falls in its relation with the socio-economic context of its publication in 2001, namely the economic recession that characterizes the earliest decade of the 21st century. The analysis will be based on historical approach’s assumption of the correlation between literary works and social context in which they are produced. Intrinsically, the novel is dissected into two levels. They are surface level (form) and deeper level (content). The results of the analysis are in the form of philosophical speculations of the novel, which are believed to follow the mood of the early 21st century, including 1) disillusionment to social mobility, 2) incredulity to human agency, and 3) romantic tendencies. This novel’s reaction to the decline of capitalism in the early 21st century seems to be similar to early romantic reaction to the rise of capitalism by returning to nature and resorting to external forces whether divine entity or otherwise.Keywords: 21st century novel; American economic recession; romanticism.